Resolving the problems of land‐lockedness - Glassner, Martin Ira (Geopolitics, 1997)
The professional literature on land-locked states has increased substantially in the past two decades. There is now a considerable body of writings by people in many countries around the world reporting on, inquiring into or carefully analysing most aspects of land-lockedness from various disciplinai and national viewpoints. In addition, there is a roughly equally large body of material related to land-lockedness produced by the United Nations and its organs and affiliates; by other intergovernmental organisations, including many regional and subregional groups; and by private consultants and consulting firms, chiefly in the fields of economics and engineering. © 1998 Frank Cass.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/006-296-698-491-722 tex.type: [object Object]
Keywords: dept.egm